PRÓBA OCENY EFEKTYWNOŚCI POLITYKI ZAGRANICZNEJ I BEZPIECZEŃSTWA UNII EUROPEJSKIEJ - Plata, Krzysztof (Studia Europaea Gnesnensia, 2018)
This paper aims to demonstrate the ineptitude of the European Union in implementing action to ensure security of the member states and, in consequence, pursuing effective foreign policy towards states which are indirectly involved in the relationships within the European region. The author argues the proposition through confrontation and interpretation of knowledge conveyed in expert sources.